Enhancing Bitumen Properties through Worm Mix Asphalt Additives: A Study on Physical and Rheological Characteristics - Hasan Wshyar M.; Yousif Rana A.; Jasim Abbas F.; Tayh Sady A. (E3S Web of Conferences, 2023)
This study aimed to determine how various concentrations of warm mix asphalt (WMA) additives can affect the rheological and physical characteristics of asphalt cement. Bitumen was modified by the chemical additive PAWMA® with an addition ratio of (0.2, 0.4, and 0.6), while the organic additives, Sasobit® and Kaowax®, were added at concentrations of (2, 4, and 6%) by the weight of bitumen. Bitumen hardness, softness, temperature susceptibility, viscosity, and elastic behavior have all been measured using a variety of physical and rheological tests, such as the penetration degree, softening point, penetration index, rotational viscosity, and dynamic shear rheology. This study showed that bitumen physical and rheological properties were affected differently according to the type and percentage of the WMA additive employed. The PAWMA additive, for instance, raised the bitumen penetration while Sasobit® and Kaowax® decreased the bitumen penetration degree. The inverse occurred for the softening point values. All WMA additives lowered bitumen viscosity values. Results from a dynamic shear rheometer (DSR) showed that the rutting index value (G*/Sin) rose, indicating improved rutting resistance.